Towards Predictive, Preventive, and Participatory Care: The Promise of Personalized Medicine - Janhavi Patil; Diya Aga; Sneha Yadav; Pooja Mane; Nuha Khamkar; Dhanashree Sanap (Fabad Journal of Pharmaceutical Sciences, 2026)
Personalized medicine is a transformative healthcare approach that designs prevention, diagnosis, and treatment to each individual’s unique genetic, molecular, and environmental profile. By integrating multi-omics technologies—genomics, transcriptomics, proteomics, and metabolomics—with advanced computational analytics, it enables early disease prediction, precise classification, and patient-specific therapy design. Advances in next-generation sequencing, artificial intelligence, and additive manufacturing, including 3D printing, have driven pharmacogenomic drug optimization, biomarker-guided targeted therapies, and on-demand production of customized dosage forms. Clinical applications span oncology, infectious, cardiovascular, neurological, and rare genetic diseases, improving therapeutic precision, reducing adverse effects, and enabling proactive disease management. Key benefits include more accurate drug-response prediction, fewer treatment failures, enhanced patient safety, and long-term economic savings through reduced healthcare utilization. However, widespread adoption faces challenges such as high cost, limited access in low-resource settings, and protection of sensitive genomic data. Ethical concerns—privacy, informed consent, and equitable benefit sharing—require robust regulation and public engagement. Future progress depends on expanding genomic diversity, building curated multi-omics repositories, and leveraging AI for biomarker discovery and predictive modeling. Emerging innovations in continuous manufacturing and flexible 3D printing will support individualized small-batch drug production, while adaptive policy frameworks must ensure safety, affordability, and accessibility. With coordinated scientific, technological, and ethical efforts, personalized medicine promises predictive, preventive, precise, and participatory healthcare worldwide.